1999
DOI: 10.1152/ajpregu.1999.276.1.r265
|View full text |Cite
|
Sign up to set email alerts
|

Role of nitric oxide and cGMP in human septic serum-induced depression of cardiac myocyte contractility

Abstract: Previous studies have demonstrated the existence of a circulating myocardial depressant substance during human septic shock. We have recently identified this substance as a synergistic combination of tumor necrosis factor-α (TNF-α) and interleukin-1β (IL-1β). This study utilized an in vitro cardiac myocyte assay to evaluate the potential mechanistic role of nitric oxide (NO) and cGMP in depression of myocyte contractility induced by TNF-α, IL-1β, TNF-α + IL-1β (at low concentrations), and human septic shock se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
141
2
6

Year Published

2000
2000
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(159 citation statements)
references
References 54 publications
10
141
2
6
Order By: Relevance
“…Studies examining the basis of depressed myocardial contractility in sepsis showed that TNF-a and IL-1b impair cardiac and cardiomyocyte contractility (46)(47)(48). These cytokines also induce mitochondrial injury (44).…”
Section: Discussionmentioning
confidence: 99%
“…Studies examining the basis of depressed myocardial contractility in sepsis showed that TNF-a and IL-1b impair cardiac and cardiomyocyte contractility (46)(47)(48). These cytokines also induce mitochondrial injury (44).…”
Section: Discussionmentioning
confidence: 99%
“…cGMP has a central role in many other vital processes such as retinal phototransduction, electrolyte regulation, and mediation of vascular smooth muscle tone [45,46]. Excessive cGMP production, generally through abundant NO availability, is implicated in the pathophysiology of distributive shock such as sepsis and anaphylaxis [47]. Dysfunction within the NOcGMP pathway has been implicated in certain disease states of distributive shock such as sepsis and anaphylaxis.…”
Section: Guanylyl Cyclase and Signaling By Cyclic Guanosine Monophospmentioning
confidence: 99%
“…The overproduction of NO by iNOS in sepsis results in increased production of cGMP contributing to the refractory hypotension observed with septic shock. Numerous animal studies demonstrate large increases of NO after exposure to lipopolysaccharide (i.e., endotoxin) with resultant hypotension [62][63][64][65][66][67].…”
Section: The No-cgmp Pathway In Anaphylaxis and The Role Of Methylenementioning
confidence: 99%
“…However, its role and impact on septic cardiomyopathy is still a matter of debate. Whereas disproportionate levels of NO sustain the ability of the left ventricle to fill during diastole, and thereby crucially support adequate myocardial perfusion (107,108), cardiodepressant activity of proinflammatory cytokines also seems to involve NO synthase (NOS): exposure of rat cardiomyocytes to septic sera depressed contractility (see below), but NOS inhibition restored contractility to control levels (109). Moreover, intracoronary infusion of the NO donor sodium nitroprusside impaired systolic pressure development despite improved diastolic relaxation and distensibility (110).…”
Section: Nitric Oxide and Peroxynitritementioning
confidence: 99%